Hybridization in Phlebotominae (Diptera: Psychodidae): A mini-review - dos Reis, Yago Visinho [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP] (Elsevier, 2020)
Taxonomy based only on morphology, although extremely important for the classification of sandflies, has been shown to be insufficient for the delimitation of some taxa. Thus, integrative taxonomy could play a fundamental role in clarifying these and other taxonomic issues, since data from different areas are used to aggregate greater reliability in species classification. Experimental crosses are important taxonomic tools, since the presence of reproductive barriers when associated with divergence between two evolutionary lineages, confirms the specific status of taxa based on the biological species concept. In the subfamily Phlebotominae, experimental crosses were mostly focused on the study of the Lutzomyia longipalpis complex, which helped to identify different evolutionary lineages for that group of vectors. Considering the difficulty of classifying some Phlebotominae species and the importance of hybridization studies for taxonomy, we grouped all the information associated with experimental crosses in sandflies in a mini-review. In view of the results grouped in this review, it is evident that i) experimental crossings are important tools to aggregate studies of integrative taxonomy in the Phlebotominae subfamily; ii) these analyses should be applied in the taxonomic studies of cryptic species; iii) Lu longipalpis populations have pre and/or post-zygotic reproductive barriers; iv) Lu. longipalpis represents more than one species and efforts must be applied to differentiate the taxa of the Lu. longipalpis complex; v) Phlebotomus populations do not present intraspecific reproductive barriers; vi) the absence of reproductive barriers between Ph. sergenti from Israel and Turkey (representing populations of the same evolutionary lineage) does not rule out the possible existence of cryptic species, it being necessary to perform experimental crosses between the different strains indicated by the molecular markers; and finally, vii) different species of Phlebotomus have post-zygotic barriers, confirming the specific status of Ph. duboscqi, Ph. papatasi, and Ph. bergeroti.
Keywords: Integrative taxonomy; Leishmaniasis; Reproductive isolation; Sand fly